Emotional Experiences and Expressions of Individuals in the Sri Lankan Context: The Roles of Gender, Culture and Religion - M.P. Dissanayake; A.G. Halberstadt; J.W. Kalat (The Open University of Sri Lanka, 2020)
The present study focused on exploring the emotional experiences and expressions of individuals, the variation in emotional expressions in different social relationships, and their perceptions about the cultural and religious appropriateness of expressing certain emotions. The sample consisted of 54 Sri Lankans who were selected using convenience sampling and the participants were aged between 17 to 64 years. A questionnaire was used to examine how often individuals experience basic emotions and some secondary emotions, to what extent they think that they can express these emotions, the appropriateness of expressing basic emotions to individuals in various relationships, and the appropriateness of feeling and expressing basic emotions according to their cultural and religious backgrounds. Results suggested significant gender differences in experiencing and expressing emotions. There were significant relationships between feeling and expressing some emotions. There were variations in emotional expressions in different social relationships. Findings also suggested that individuals accepted the experience and expression of some emotions according to their cultural and religious backgrounds.